Relationship between Knowledge about Food, Pregnancy Myths, Education and Anxiety in Pregnant Women at the "J" Health Center in Tangerang Regency in 2025 - Siti Maisaroh; Yuliwati Yuliwati (Jurnal Ners, 2026)
Anxiety among pregnant women remains a common problem in antenatal care and can be influenced by various factors, both in terms of knowledge and socio-cultural aspects. Knowledge about nutrition during pregnancy, beliefs about pregnancy myths, and the mother's level of education are factors that are thought to play a role in the emergence of anxiety among pregnant women. This study aims to analyze the relationship between knowledge about food, belief in pregnancy myths, and education with anxiety in pregnant women at the "J" Community Health Center in Tangerang Regency in 2025. This study uses a quantitative approach with a descriptive analytical design and a cross-sectional method. Data collection was conducted in April 2025 on 67 pregnant women who visited the health center, using accidental sampling. Data were collected using a closed questionnaire and analyzed univariately and bivariately using the chi-square test. The results of the analysis showed that mothers' knowledge about food had a significant relationship with anxiety in pregnant women (p = 0.005). In addition, belief in pregnancy myths was also significantly related to anxiety in pregnant women (p = 0.001). Maternal education also showed a significant relationship with maternal anxiety (p = 0.002). Pregnant women with less knowledge, who still believed in pregnancy myths, and who had lower education tended to experience anxiety compared to pregnant women who had good knowledge, did not believe in pregnancy myths, and were more educated.Based on these results, it can be concluded that knowledge, belief in pregnancy myths, and education play a role in the level of anxiety experienced by pregnant women. Health education tailored to the educational background and culture of the community needs to be improved as an effort to reduce anxiety during pregnancy